Predicting the Outcome of Total Knee Arthroplasty Using the WOMAC Score: A Review of the Literature - Walker, Lucy Camilla; Clement, Nick D.; Deehan, David J. (The Journal of Knee Surgery, 2019)
It is estimated that up to a third of recipients of total knee arthroplasty (TKA) experience chronic pain postoperatively. However, there are no clear indications within the literature that predict which patients are at higher risk of being dissatisfied with their TKA. The Western Ontario and McMaster University Osteoarthritis Index (WOMAC) is one of the most commonly used, patient-reported outcome measures in patients with lower limb osteoarthritis. This review discusses the available evidence surrounding the predictability of the outcome of TKA using the WOMAC score as well as considering further patient factors that have been implicated in the level of improvement post TKA. It may be concluded from the available literature that a combination of knee scores and patient factors would be the most accurate way of predicting those patients most likely to have a good outcome from their TKA. There is some disparity within the literature about which patient factors and reported outcome measure scores lead to a positive postoperative outcome. Patient expectations following the procedure also need to be evaluated, as objective measures on a scoring system do not necessarily equate with the subjective patient experience.
Keywords: total knee arthroplasty; outcome measures; satisfaction